Reading Comprehension Improvement through Question and Answer Relationship (QAR) Method - Rizal Arisman; Baharudin Adu; Nur Adha Fitriyani Ambotang (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2021)
The objective of this research was to find out the significant difference in reading comprehension between students who were taught using the Question and Answer Relationship (QAR) method and those who were taught using the conventional method. This research used a quantitative approach with the experimental design of the quasi-experimental method. The instrument of this research was a test, dividing into pretest and posttest. In this research, it was found that the experimental group's mean pretest score was in a low category and the posttest score was in a good category. While the control group's mean pretest score was in a low category, but the posttest score was in the moderate category. The result of the Independent Sample T-Test indicated that the tcount was 4.549 which was higher than ttable (2.021) and the score of sig. (2-tailed) was 0.000 which was less than 0.05. This research thus concluded that there was a significant difference in reading comprehension achievement between students who were taught using the Question and Answer Relationship (QAR) method and those who were taught using the conventional method.